Implications of Changes in Spatial Utilization for Socio-Economic Changes in Tanjung Merdeka Village, Tamalate District, Makassar City - Siti Fatimah Umamit; Despry Nur Annisa Ahmad; Musdalifah Rahman; Andi Idham Asman; Harry Hardian Sakti (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
One of the major cities in Indonesia that is currently experiencing a significant population increase is Makassar City. The increase in population in Makassar City is always followed by the increase in residential and non-settlement buildings. This can be seen in the development of the Tanjung Merdeka Sub District which is increasingly experiencing an increase in development activities. In addition, land prices in the area have also skyrocketed and caused massive, uncontrolled land conversion, and also affected the welfare order of local communities in the region. The objectives of the study are; (1) to analyze the land use changes in the Tanjung Bunga Metro Area; (2) to analyze the socio-economic changes of local community communities in the Tanjung Bunga Metro Area; (3) Analyze the implications to the extent of changes in the use of space on socioeconomic changes in local community communities. The analysis methods used are spatial analysis techniques, qualitative statistics, and quantitative descriptive. The results of this study are in the form of recommendations for the direction of space utilization in realizing welfare in local communities in the Metro Tanjung Bunga Area.